Narrowband UVB phototherapy reduces TNF production by B‐cell subsets stimulated via TLR7 from individuals with early multiple sclerosis. Issue 10 (15th October 2020) - Trend, Stephanie; Leffler, Jonatan; Cooper, Matthew N; Byrne, Scott N; Kermode, Allan G; French, Martyn A; Hart, Prue H
Abstract: Objectives: At the end of a 60‐day course of narrowband UVB phototherapy, administered to individuals with early multiple sclerosis, there were changes in the relative proportions of circulating B‐cell subsets. This study investigated phototherapy‐associated changes to cytokine responses of B cells when exposed to a TLR7 ligand. Methods: PBMCs from participants of the PhoCIS (Phototherapy for Clinically Isolated Syndrome) trial taken before (day 1) and after phototherapy for 8 weeks (day 60) were incubated with, or without, the TLR7 ligand, R848, for 18 h. Production of TNF and IL‐10 in seven B‐cell subsets was examined, with cytokine responses in each individual at day 60, adjusted for responses at day 1. Paired PBMCs were from participants administered phototherapy ( n = 7) or controls ( n = 6). Results: At day 60, significantly fewer B cells, particularly marginal zone‐like B cells (CD27 + /IgD + ), from participants administered phototherapy produced TNF in response to TLR7 stimulation. When responses by seven B‐cell subsets were analysed together using multivariate methods, a phototherapy‐specific signature was observed. An increased responsiveness from day 1 to day 60 in IgM‐only memory B cells (CD27 + /IgD − /IgM + ) after TLR7 stimulation also predicted slower progression from CIS to MS. Phototherapy was without significant effect on B‐cell IL‐10 production. Conclusions: Reduced TNF responses after TLR7 stimulation in marginal zone‐like B cells from participants administered phototherapy suggested treatment‐associated priming effects that were detected upon subsequent polyclonal B‐cell activation. Changes in responsiveness to TLR7 stimulation also suggested that IgM‐only memory B cells may be important in conversion from CIS to MS. Abstract : Phototherapy was tested to prevent or delay individuals with clinically isolated syndrome converting to multiple sclerosis. This study investigated the functional impact of phototherapy on circulating B cells. In addition to modulating the proportion of circulating B‐cell subsets, phototherapy reduced the ability of B cells to respond to TLR7 stimulation with pro‐inflammatory TNF production suggesting that phototherapy may limit polyclonal B‐cell activation.